Good response to methotrexate is associated with a decrease in the gene expression of ABCG2, a drug transporter, in patients with rheumatoid arthritis. Issue 6 (2nd November 2021) - Muto, Satoshi; Minamitani, Nana; Ogura, Takehisa; Nakajima, Arata; Nakagawa, Koichi; Masaka, Toru; Hiura, Sumiko; Kobayashi, Hideki; Kato, Hiroyoshi; Kameda, Hideto
Abstract: Objectives: Methotrexate (MTX) is used as an anchor drug in the treatment of rheumatoid arthritis (RA), although more than a half of the patients with RA require additional treatments. We designed a prospective study involving two medical centers in Japan to examine the association between the expression of MTX-related genes including a drug transporter ATP-binding cassette sub-family G member 2 (ABCG2) gene and the clinical response to MTX in MTX-naive patients with RA. Methods: The primary endpoint of this study was good response based on the European League Against Rheumatism (EULAR) response criteria by Disease Activity Score using 28-joint count (DAS28). We evaluated the association between the baseline expression of six genes involved in the intracellular pharmacokinetics of MTX, including ABCG2, as well as their temporal changes, and the clinical response at week 12 from the initiation of MTX. Results: Based on the clinical response at 12 weeks after the initiation of MTX, 24 patients were classified into good responders ( n = 9) and non-good responders ( n = 15; 10 moderate responders and 5 non-responders) groups. A univariate logistic regression analysis of the baseline gene expression levels to predict the EULAR good response at week 12 showed a significant association with ABCG2 expression alone. Furthermore, the rate of baseline expression of ABCG2 mRNA above the cut-off value determined using a receiver operating characteristic curve was higher in good responders than in non-good responders ( p = .012). Moreover, ABCG2 expression decreased in almost all good responders, but not in non-good responders, after MTX treatment for 12 weeks (median −76% vs. +41% from baseline, respectively; p = .011). The ABCG2 expression level did not correlate with DAS28 at baseline or week 12. Conclusions: Our study revealed that good response to MTX is associated with a decrease in the expression of ABCG2 in patients with RA.